Implementation of utilizing student interests and talents in improving student learning outcomes - Rahmadani, Rahmadani; Jarkawi, Jarkawi; Yuliansyah, Muhammad (ARKA INSTITUTE, 2023)
School as a place of learning should be a place to develop students' interests and talents. The important thing in developing students' interests and talents is to have an awareness of their interests and talents. This awareness will lead him to strategic choices in the future related to the chosen field of study, a conducive learning environment and the choice of profession according to his interests and talents. Knowledge of these interests and talents needs to be facilitated by schools, parents and the community. This study aims to determine the application of utilizing students' interests and talents in improving student learning outcomes. This type of research includes qualitative research and uses descriptive analysis techniques. The results of this study can be said that the implementation of the utilization of interests and talents is carried out when students register and choose the majors of interest. Students also choose intra and extracurricular activities to support their interests and talents. In addition, students are also asked to fill out a student needs questionnaire as a basis for counseling services. However, at the implementation level, the use of interest has not been accompanied by a special aptitude test to support student interest.